Plastid Alternative Oxidase (PTOX) Promotes Oxidative Stress When Overexpressed in Tobacco - Heyno, Eiri (American Society for Biochemistry and Molecular Biology, 2009)
Photoinhibition and production of reactive oxygen species were studied in tobacco plants overexpressing the plastid terminal oxidase (PTOX). In high light, these plants was more susceptible to photoinhibition than wild-type plants. Also oxygen-evolving activity of isolated thylakoid membranes from the PTOX-overexpressing plants was more strongly inhibited in high light than in thylakoids from wild-type plants. In contrast in low light, in the PTOX overexpressor, the thylakoids were protected against photoinhibition while in wild type they were significantly damaged. The production of superoxide and hydroxyl radicals was shown by EPR spin-trapping techniques in the different samples. Superoxide and hydroxyl radical production was stimulated in the overexpressor. Two-thirds of the superoxide production was maintained in the presence of DNP-INT, an inhibitor of the cytochrome b(6)f complex. No increase of the SOD content was observed in the overexpressor compared with the wild type. We propose that superoxide is produced by PTOX in a side reaction and that PTOX can only act as a safety valve under stress conditions when the generated superoxide is detoxified by an efficient antioxidant system.